(untitled) (International Journal of Ayurveda and Pharma Research, 2021)
Mahadalu anupana is one of the most common Dalu anupana (fluid vehicles for medicine which is prepared by tender leaves and some other additives) of the traditional medical system in Sri Lanka and this Anupana is one of Anupana mentioned under Chandra kalka. Mahadalu anupana is used in many ailments with or without Kalka in traditional medical system. This research work is mainly based on the main twelve ingredients of the formulation of Mahadalu anupana without the additives (sugar, ghee, orange juice, breast milk, sandalwood and Strychnos potatarum) which has mentioned in the authentic text of Vatika prakaranaya/ Deshiya beheth guli kalka potha in Sri Lankan traditional medicine. In this study, organoleptic properties and selected phytochemical studies were performed for future standardization of drug. Phytochemicals are bioactive compounds obtained from the plants and has therapeutic potential. The organoleptic properties indicated of this Anupana as follow; colour: brownish green, odour: strong aromatic, taste: astringent and the texture were liquid. The phytochemical analysis study was done for the water extract of Mahadalu anupana. This study has revealed that the presence of alkaloids, tannins, flavonoids, saponins, terpenoids, glycosides and carbohydrates qualitatively in main ingredients of Mahadalu aupana but steroids and proteins were not reported. It was concluded that the Mahadalu anupana (without additives) were rich in phytochemicals with medicinal significant and this study results can be utilized in future consistency studies of Mahadalu anupana.